METHODS OF THE DETERMINATION OF THE HYDROGEOLOGICAL PARAMETERS ON THE RESULTS OF THE EXPERIMENTAL CONSTANT-RATE PUMPING TESTS FROM THE LAYERED AQUIFERS WITH OVERFLOW - M. M. Burakov (Известия высших учебных заведений: Геология и разведка, 2018)
The methodical aspects of the processing and interpreting the results of the experimental filtration tests of the layered strata by the constant-rate pumping tests have been developed. Determination of the filtration and volumetric characteristics of the tested pressure aquifer has been proposed on the basis of the author's method based on the results of tracking the drawdown of the piezometric level of the groundwater in the wells of the experimental cluster at the initial stage of the pumping. Methods for interpreting the experimental data of the second and third stages of the constant-rate pumping test for the calculation of the flow parameters have been proposed.